2010
DOI: 10.1087/20100206
|View full text |Cite
|
Sign up to set email alerts
|

Write when hot — submit when not: seasonal bias in peer review or acceptance?

Abstract: ABSTRACT. At a top psychology journal, Psychological Science (PS),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…The investigation started a discussion in which Hartley 2 found 'no significant differences between the numbers of articles submitted in the winter and the summer months' (p. 29) for two anonymized journals, presumably also from the field of psychology in 2008 and 2009. This result is in agreement with the original findings of Shalvi et al 1,3 for three years of the journal Personality and Social Psychology Bulletin (PSPB), but in contrast to their observations for four years of the journal Psychological Science (PS) wherein a summer peak of the number of submissions was not accompanied by a respective peak of the number of accepted manuscripts, which led to the conclusion that one should better delay the submission of a manuscript during the summer. Bornmann and Daniel 4 have recently analyzed their data from a comprehensive research project on the peer-review process of the journal Angewandte Chemie International Edition (AC-IE) for the year 2000 and found that while the number of submitted manuscripts fluctuated strongly, 'there was a statistically non-significant association between number of submissions in a month and the likelihood of a manuscript's acceptance for publication' (p. 327), i.e.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…The investigation started a discussion in which Hartley 2 found 'no significant differences between the numbers of articles submitted in the winter and the summer months' (p. 29) for two anonymized journals, presumably also from the field of psychology in 2008 and 2009. This result is in agreement with the original findings of Shalvi et al 1,3 for three years of the journal Personality and Social Psychology Bulletin (PSPB), but in contrast to their observations for four years of the journal Psychological Science (PS) wherein a summer peak of the number of submissions was not accompanied by a respective peak of the number of accepted manuscripts, which led to the conclusion that one should better delay the submission of a manuscript during the summer. Bornmann and Daniel 4 have recently analyzed their data from a comprehensive research project on the peer-review process of the journal Angewandte Chemie International Edition (AC-IE) for the year 2000 and found that while the number of submitted manuscripts fluctuated strongly, 'there was a statistically non-significant association between number of submissions in a month and the likelihood of a manuscript's acceptance for publication' (p. 327), i.e.…”
Section: Introductionsupporting
confidence: 92%
“…the citation data for 15,478 submissions, statements about the different quality remain simply speculation for the present sample. It is clear from the data, however, that the high number of submissions in July is accompanied by a high acceptance rate and thus does not create an entrance barrier in striking contrast to the conclusions by Shalvi et al 1 The available data also enabled me to analyze the decision time, i.e. the time between submission and acceptance of a manuscript.…”
Section: Discussionmentioning
confidence: 91%
“…In an earlier article in this journal 1 we presented data obtained from two psychology journals suggesting that in one of them (Psychological Science), but not the other (Personality and Social Psychology Bulletin), it might be wise not to submit during the summer months. We based this conclusion on a discrepancy we observed: while contributors to PS submit mostly in the summertime, the number of accepted papers does not vary across the months of the year.…”
mentioning
confidence: 99%
“…4 Given these incentives, it is no surprise that academia makes for strange bedfellows. There are even those authors who have calculated the presence of seasonal shifts in acceptance ratios (Shalvi et al, 2010), so as to optimize publication success (until competitors have caught up with the trend).…”
Section: The Author-editor-reviewer Trinity Of Academic Writingmentioning
confidence: 99%